PEMANFAATAN APLIKASI PEMBELAJARAN DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR - Vika Wiguna Pratama; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology has brought major changes in the field of education, particularly through the utilization of digital learning applications. The use of applications such as Google Classroom, interactive multimedia, mobile learning, and web-based learning platforms has proven effective in improving students’ motivation, engagement, and learning outcomes. This article aims to analyze the utilization of digital learning applications in improving student learning outcomes by examining examples from online news articles and journals. The method used in this study is a literature review by collecting data from scientific articles and online educational news sources. The analysis results indicate that the use of digital learning applications has a positive impact on students’ understanding of learning materials, participation, and the effectiveness of the learning process. In addition, several spelling and writing errors were found in the analyzed news sources and articles, including incorrect capitalization, nonstandard words, and improper punctuation. Therefore, the use of digital technology should be balanced with good language literacy skills so that educational information can be conveyed effectively and correctly.